The impact of suicide prevention education programmes for nursing students: A systematic review. (22nd June 2020) - Ferguson, Monika; Reis, Julie; Rabbetts, Lyn; McCracken, Tara; Loughhead, Mark; Rhodes, Kate; Wepa, Dianne; Procter, Nicholas
Abstract: The purpose of this systematic review was to locate and synthesize peer‐reviewed evidence regarding the effectiveness of providing suicide prevention education to nursing students. Systematic searches were conducted in seven databases (EMBASE, EmCare, Joanna Briggs, MEDLINE, PsycINFO, Scopus, and Web of Science). Results were screened in duplicate at two stages: title and abstract, and full text. Critical appraisal and data extraction were also completed in duplicate. Initial database searching yielded 303 results. Following the addition of seven records from relevant reference lists, and the removal of duplicates, a total of 118 results were included for screening. Eight articles were deemed eligible for inclusion in this review; most ( n  = 5) were quantitative. While all were conducted within university settings, half were stand‐alone education sessions, while the remaining were integrated with existing programmes/courses. The types of education programmes varied considerably across studies, with only three being established, evidence‐based programmes. The studies explore a range of outcomes, which have been narratively categorized as enhanced skills, abilities, and self‐confidence; development of positive attitudes and beliefs; acquisition of knowledge; and programme experience and evaluation. While there is a small body of evidence indicating that suicide prevention education programmes contribute to improvements in skills, abilities, self‐confidence, and attitudes among nursing students, the variability in educational interventions and outcomes, coupled with short‐term evaluation time frames, makes it difficult to fully understand the impact of this important suicide prevention strategy.